Auditoria administrativa y su relación con el proceso de rendición social de cuentas de la unidad educativa "Mocache", año 2013 - Yumiluisa Moran, Ligia Elena (2015)
This research was conducted at the Education Unit "Mocache" which is located in the Allotment Luis Fernando Av. Walter Andrade Fajardo and perimeter, is an educational institution of the canton Mocache in the province of Los Rios, whose geographical position is 11.01 'S latitude and 79.29'O South, the overall objective is to conduct a Management Audit and their relation to the processes of Social Accountability for improvement and support staff of the Education Unit "Mocache". Year 2013. It was identified that the organizational structure of the Education Unit “Mocache” are consistent with the principles, laws and internal regulations and comply with the standards set by the Ministry of Education. It is established that the degree of trust and risks made to the Education Unit Mocache allowed to establish the shortcomings found in the management processes, a risk audit of 2.13%, determining it as acceptable was obtained. It was determined that the management indicators established the Educational Unit has 40% of male teachers; while 60% are women; It has done 45% of seminars given during the year; have a 94.04% of students promoted to the next grade, also expressed that the money issued by the government is not enough to cover the needs, determining a 7.61% default.